Complete A+ guide to IT hardware and software a CompTIA A+ Core 1 (220-1101) & CompTIA A+ Core 2 (110-1̀102) textbook - Schmidt, Cheryl A. 1961-; Lee, Christopher A. (Pearson, 2022)
Master IT hardware and software installation, configuration, repair, maintenance, and troubleshooting and fully prepare for the CompTIA® A+ Core 1 (220-1101) and Core 2 (220-1102) exams. This is your all-in-one, real-world, full-color guide to connecting, managing, and troubleshooting modern devices and systems in authentic IT scenarios. Its thorough instruction built on the CompTIA A+ Core 1 (220-1101) and Core 2 (220-1102) exam objectives. Award-winning instructor Cheryl Schmidt also addresses widely-used legacy technologies making this the definitive resource for mastering the tools and technologies you'll encounter in real IT and business environments. Schmidt's emphasis on both technical and soft skills will help you rapidly become a well-qualified, professional, and customer-friendly technician.
Includes index
Keywords: Computing Technology Industry Association -- Textbooks -- Examinations; Microcomputers -- Textbooks -- Maintenance and repair -- Examinations; Computer technicians -- Textbooks -- Certification; Computer networks -- Textbooks -- Examinations; Computing Technology Industry Association; Computer networks; Examinations; Computer technicians; Certification; Examinations; Microcomputers; Maintenance and repair; Examinations; Textbooks